Bridging the Gap between Genotype and Phenotype via Network Approaches - Kim, Yoo-Ah; Przytycka, Teresa M. (Frontiers in Genetics, 2013)
In the last few years we have witnessed tremendous progress in detecting associations between genetic variations and complex traits. While genome wide association studies have been able to discover genomic regions that may influence many common human diseases, these discoveries created an urgent need for methods that extend the knowledge of genotype-phenotype relationships to the level of the molecular mechanisms behind them. To address this emerging need, computational approaches increasingly utilize a pathway centric perspective. These new methods often utilize known or predicted interactions between genes and/or gene products. In this review, we survey recently developed network based methods that attempt to bridge the genotype-phenotype gap. We note that although these methods help narrow the gap between genotype and phenotype relationships, these approaches alone cannot provide the precise details of underlying mechanisms and current research is still far from closing the gap.